Human Resources Competence in The Field of Tourism Destination Development Tomohon City Tourism Department - Robot, Angel P. M.; Kairupan, Sisca Beatrix; Mandagi, Marthinus (Technium Social Sciences Journal, 2021)
The success of implementing programs and activities of a government agency to achieve the maximum target and by the desired output is primarily determined by one of the supporting components in a government agency, namely the competence of human resources. This study aims to examine and describe the Competence of Human Resources at the Department of Tourism for the Development of Tourism Destinations in the City of Tomohon, Section of Tourism Destination Management. The author uses indicators that characterize Knowledge Competence, i.e., skill and Behaviours of performance that can be observed, measured, and evaluated. The research method used is a qualitative approach with data collection techniques through observation, interviews, and documentation. Data analysis used an interactive model with data reduction, data presentation, and conclusion drawing. The results of this study are that Human Resources in the Tourism Destination Governance Section have competence in carrying out the duties and functions of tourism destination governance in Tomohon City.